Analisis Permintaan Ekspor Pakaian Jadi Indonesia Ke Amerika Serikat Tahun 1991-2016 - Dinata, I Gusti Ayu Yana; Arka, Sudarsana (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2019)
E xport is one of the international trade activities that has an important role for the economy of a country. One of Indonesia's export products to the United States is textile products, namely apparel products. This study aims to analyze the simultaneous and partial effect of United States dollar exchange rates, prices, United States Gross Domestic Product and import quotas on Indonesian apparel exports to the United States in 1991-2016. The data used in this study is secondary data. The analysis technique is multiple linear regression analysis. Test results show that the United States dollar exchange rate, prices, United States Gross Domestic Product and import quotas simultaneously have a significant effect on Indonesian apparel exports to the United States. The partial test results show that the US dollar exchange rate and the United States GDP have a positive and significant impact on Indonesia's apparel exports to the United States. Prices have a negative and significant effect on Indonesia's apparel exports to the United States. The abolition of import quotas increases Indonesia's apparel exports to the United States.